2017
DOI: 10.1515/pomr-2017-0062
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Method and Neural Network Model Parallel Implementation of Multi-Layer Neural Network Based on Cloud Computing for Real Time Data Transmission in Large Offshore Platform

Abstract: With the rapid development of electronic technology, network technology and cloud computing technology, the current data is increasing in the way of mass, has entered the era of big data. Based on cloud computing clusters, this paper proposes a novel method of parallel implementation of multilayered neural networks based on Map-Reduce. Namely in order to meet the requirements of big data processing, this paper presents an efficient mapping scheme for a fully connected multi-layered neural network, which is tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The evaluation of classroom teaching quality in colleges and universities is relatively backward, and the research on it in some countries is relatively advanced [ 4 ]. Hu and Qin found that most of the online education still follow the traditional teaching ideas, ignoring the characteristics and differences of different students' online education ability, so the online education classroom teaching effect in colleges and universities cannot reach the optimal state [ 5 ]. Arciszewskl and Ziarko put forward an adaptive classroom teaching model of online education in colleges and universities based on multistrategy technology.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of classroom teaching quality in colleges and universities is relatively backward, and the research on it in some countries is relatively advanced [ 4 ]. Hu and Qin found that most of the online education still follow the traditional teaching ideas, ignoring the characteristics and differences of different students' online education ability, so the online education classroom teaching effect in colleges and universities cannot reach the optimal state [ 5 ]. Arciszewskl and Ziarko put forward an adaptive classroom teaching model of online education in colleges and universities based on multistrategy technology.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, a lot of data have been produced in the comprehensive performance analysis and bearing capacity test of the bridge prestress under fatigue load [4]. How to extract, collect, and store the mechanical properties of the bridge through these redundant data has become the main research direction of the research on the mechanical property change and ultimate load effect of the bridge prestress under the fatigue load [5]. Scholars conducted fatigue and postfatigue static load tests on 11 partially prestressed concrete test beams.…”
Section: Introductionmentioning
confidence: 99%
“…LSTM neural network is long short memory neural network, and CRF neural network is conditional random field algorithm. According to the combination of the features of the two algorithms, the classification can be accurately distinguished according to the semantic and grammatical relationship between the upper and lower texts [ 18 ]. Finally, the purpose of data analysis and detection is achieved.…”
Section: Introductionmentioning
confidence: 99%